Applying value engineering in slope failure on road embankment remedial work - Nazib Faizal, 1979-; Sarajul Fikri Mohamed, supervisor; Fakulti Alam Bina (2011)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan) - Universiti Teknologi Malaysia, 2011